[Plane on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a small airplane surrounded by people at Heimaey Airport. The red, white, and grey striped plane sits on a brown platform at the bottom of the photograph. The group of people hold boxes and luggage, putting them on the plant. A white van sits along the left edge of the photograph. A grey mountain sits in the background, covered in lines of grey rock.